FUNDAMENTAL CONCEPTS OF FINANCIAL ACCOUNTING AND DIALECTIC OF THEIR DEVELOPMENT: MACROECONOMIC CONCEPT, MICROECONOMIC CONCEPT - Antonova, O.V.; Sh. Kremer, N.; Lukyanenko, G.I; Martyinenko, N.N.; Melnikova, L.A. (Scientific Journal of Pedagogy and Economics, 2020)
At the moment, the advancement of accounting is recognizably driven by the development of its theory and methods in order to assess the existing and recently emerging accounting concepts and expand the theoretical, regulatory, and methodological framework of accounting based on such concepts. In accounting, framework developments put forward new accountable items, and new concepts lead to a brand-new approach to the scientific research of accounting as a science. Thus, research should be conducted from the perspective of a comprehensive analysis of the existing Concept for the Development of Accounting, which is an integral component of the institutional system represented by the structural elements of the accounting system and related systems arranged in a strictly defined order [1,4,17]. The theory and methods of accounting are implemented through the development and use of certain concepts. The requirement to use the accounting concepts is explained by the fact that the accounting practice in Russia lags far behind the recently established requirements for the quality of accounting information as driven by the current processes of globalization and integration of the Russian Federation into the global economy. This requires a separate approach to understanding the theoretical and methodological foundations of accounting from the perspective of institutionalism [5,13,20]. The method is considered in the work as a point of view on the structure and development of accounting. Elements of methodological institutionalism are used as a justification of the position under consideration. When considering the impact on the development of accounting of institutional factors, a number of research tasks are set, including determining the role of the organization of accounting, institutional factors, the possibility of institutional organization of accounting, determining the subject, object, subject and scientific status of accounting. The authors revealed what theoretical and methodological concepts are: forms of accounting organization, schemes, models, methods of cognition, or is it all taken together.